(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
A split-plot experiment was conducted at the DemonstrationFarm of the Faculty of Agriculture, University of Khartoum, during theperiod January 1999 - June 2000 to study the effect of water stress andcutting frequency on seed production of alfalfa (Medicago sativa L.).Three irrigation intervals (7, 14 and 21 days) were assigned to the mainplots and designated I1 , I2 and I3 , respectively, and three cuttingfrequencies; namely, 21, 28 and 35 days were assigned to the subplots andgiven the symbols C 1 , C 2 and C 3 , respectively. Data were collected onnumber of racemes per plant, number of pods per raceme, number ofseeds per pod, 1000-seed weight and final seed yield. Correlation analyseswere carried out between yield and some of its components. The resultsrevealed that shorter irrigation intervals (7 and 14 days) were significantlybetter than the longer interval (21 days), and the 35 days cuttingfrequency was the best for seed yield. Neither the number of seeds perpod nor the 1000-seed weight were affected by the cutting intervals.However, the former was significantly affected by irrigation intervals.Mean seed yield for the irrigation intervals was 77.9, 86.2 and 41,4 kg/hafor I1 , I2 and I3 , respectively. On the other hand, cutting frequenciesresulted in seed yields of 38.1, 78,2 and 89.2 kg/ha for C 1 , C2 and C3 ,respectively. Correlation analyses showed that seed yield was highlycorrelated with 1000-seed weight and number of seeds per pod.